2018
DOI: 10.1016/j.pmedr.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

From awareness to behaviour: Testing a hierarchy of effects model on the Australian Make Healthy Normal campaign using mediation analysis

Abstract: The Make Healthy Normal mass media campaign was a three-year campaign launched in 2015 in New South Wales (NSW), Australia to address community norms around overweight and obesity. It was underpinned by a hierarchy of effects model; a commonly used framework in campaigns but one that has rarely been tested. The campaign evaluation included a cohort study of NSW adults, surveyed three times over 12 months (n = 939 at Wave 3). This study tested the campaign's hierarchy of effects model, which theorized that part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…This is in contrast to findings from the high income countries where patients typically have a good understanding of their disease, its severity, the system involved and the prognosis [16,17]. Low awareness levels and understanding of the disease affect health seeking behaviour and/or health practices; this is often emphasised by theoretical models such as the Hierarchy of Effects Model (HOEM) which proposes that 'proximal' variables like awareness are causally linked to 'distal' variables like behaviour change through a series of intermediate measures, including social norms, attitudes and intentions [18,19]. Similarly psychological theory-based models like the Health Belief Model (HBM) and the Integrated Behaviour Model (IBM) which incorporates the Theory of Planned Behaviour (TPB) also emphasise knowledge as a key determinant of health behaviour change [20].…”
Section: Interpretation In the Light Of Published Literaturementioning
confidence: 99%
“…This is in contrast to findings from the high income countries where patients typically have a good understanding of their disease, its severity, the system involved and the prognosis [16,17]. Low awareness levels and understanding of the disease affect health seeking behaviour and/or health practices; this is often emphasised by theoretical models such as the Hierarchy of Effects Model (HOEM) which proposes that 'proximal' variables like awareness are causally linked to 'distal' variables like behaviour change through a series of intermediate measures, including social norms, attitudes and intentions [18,19]. Similarly psychological theory-based models like the Health Belief Model (HBM) and the Integrated Behaviour Model (IBM) which incorporates the Theory of Planned Behaviour (TPB) also emphasise knowledge as a key determinant of health behaviour change [20].…”
Section: Interpretation In the Light Of Published Literaturementioning
confidence: 99%
“…Factors such as emotions and levels of knowledge and awareness significantly contribute to a person's attitude/belief formation and decisionmaking process, ultimately influencing behavior changes. [54][55][56] Using this framework, assessments of intervention efficacy typically fell in 5 domains: (1) Behavior, (2) Intention, (3) Attitudes/ Beliefs/Perception, (4) Knowledge/Awareness, and (5) Emotion/Reaction.…”
Section: Assessmentsmentioning
confidence: 99%
“…Wan et al [22] considered the awareness of consequences as an underlining factor for behavioral intention, but found that even though the connection was positive and significant, the influence was low. Furthermore, Kite et al [53] underlined the fact that some variables, such as awareness, are casually linked to distant outcomes such as behavior through the connection of other variables such as attitudes, social norms, intentions. Meng et al [34] included environmental awareness as part of the environmental attitudes with a direct influence on the residents' disposal behavior.…”
Section: Awarenessmentioning
confidence: 99%